Mycotoxins, invisible danger of feedstuff with toxic effect on animals - Buszewska-Forajta, Magdalena (Toxicon (Oxford), 2020)
Mycotoxins are low-molecular weight compounds produced mainly by fungi, with Fusarium and Aspergillus origin. Secondary, metabolites, are mostly found on plants. However, the contamination of the feed and forage has been also reported. Because of their pharmacological activity, mycotoxins can be used as chemical warfare agents, drugs or growth promotants. Additionally, mycotoxins are found as one of the most dangerous genotoxic factors which cause the damage of DNA and lead to disease development. This review includes the knowledge of mycotoxins as both, an invisible danger of forage and as food additives. Special emphasis shall be given on mycotoxins with proven cancerogenic activity; including aflatoxins, fumonisins, ochratoxins, trichothecenes, and zearalenone. Factors such as species, mechanisms/modes of action, metabolism, and defense mechanisms were taken into account. The main concern was focused on zearalenone characterization, because of its estrogenic activity, caused by structural similarity to estrogens, naturally occurring in cells. By binding to estrogenic receptors, toxins are, accumulated in organisms and long-term exposure may cause the disturbances, especially in the reproductive system. The next part of this paper contains the description of main strategies of toxins determination. Finally, in the review, several potential methods for the dioxins neutralization were discussed. •Characteristic of mycotoxins with proved cancerogenetic activity.•Main strategies for the determination of toxins with fungi origin.•Potential methods for neutralization of mycotoxins.